Employee Engagement and Its Impact on Employee Retention - Pahilajani, Sunil (Digital Repository of Theses, 2025)
With large-scale growth in the number of firms, be it services, manufacturing or other smallscale industries and a milieu of uncertainty and high competition, human capital challenges are on the rise. Many modern organizations are embroiled in the talent war and facing challenges in sustaining the employees’ engagement levels. This study investigated the relationship between employee engagement and employee retention alongside measuring for the effects of demographic variables on both the constructs. The study carried out in three segments wherein an attempt is made to empirically identify the factors of employee engagement. The second part of the study was concerned with ascertaining the effects of employee engagement on employee retention. And the third part assessed the significant differences (if any) of demographic variables on both the constructs. Results indicated that five factors loaded onto the employee engagement construct and all found to be significant. Overall, there was a positive and strong effect of employee engagement on employee retention. Likewise, the study also looked for possible effects of each of the factors of employee engagement on employee retention and found that job resources had a higher impact on employee retention. Apart from the assessment of the impact of these variables on each other, the study also explored the performance of each of these constructs against a host of demographic variables. The results indicated that significant differences were found to exist across age, gender, marital status, income, industry, and geographical region, level of education and level of experience. The conclusions and inferences thus drawn from the current study will offer foundational help to organizations to design responsible human resource policies and practices. The study also predicts important trends both at the organizational and social levels. The findings of this study can have a seemingly large impact on the contemporary organizations and can prudently provide a framework for undertaking further academic research. Key Words: Employee Engagement, Employee Retention, Quantitative Research.